Potret Perilaku Konsumtif Mahasiswa Pengguna E-Wallet Berdasarkan Intensitas dan Perbedaan Gender - Fathullah, Muhammad Zikri; Putri, Nayla; Anugrah, Rangga; Khairunnisa, Durriyah (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2026)
This study aims to examine the consumptive behavior of students who use e-wallets by analyzing their level of consumptive behavior, differences based on gender, and the relationship between e-wallet usage intensity and consumptive behavior. This research employs a quantitative approach with associative and comparative designs. The population consists of students of the Faculty of Economics and Business, Universitas Tanjungpura, with a sample of 50 respondents selected using purposive sampling. Primary data were collected through an online questionnaire using nominal and ordinal scales. Data were analyzed using non-parametric statistical tests, namely the Wilcoxon Signed Rank Test, the Mann-Whitney U Test, and Spearman Rank correlation. The results show that students’ consumptive behavior is generally at a moderate level and is statistically not categorized as high. There is no significant difference in consumptive behavior between male and female students. The results also show no significant relationship between e-wallet usage intensity and students’ consumptive behavior. These findings indicate that although students actively use e-wallets, they tend to use them as efficient payment tools rather than as instruments of impulsive consumption. Students’ consumptive behavior appears to be more strongly influenced by internal factors such as financial awareness, self-control, and financial literacy than by the intensity of e-wallet usage or gender differences.